Genotype x environment interaction and yield stability of normal and biofortified maize inbred lines in stress and non-stress environments - Goredema-Matongera, Nakai; Thokozile Ndhlela; Biljon, Angeline van; Labuschagne, Maryke T. (Informa UK Limited, 2023)
Breeding for nutrient-dense maize cultivars is reliant on introductions of exotic inbred lines enhanced with high levels of the targeted nutrients. Sometimes, the exotic nutrient donor germplasm may not adapt well in new growing environments, thereby reducing seed production when used in hybrid combinations. Therefore, evaluating introduced trait donors for adaptation, through genotype × environment interaction (GEI) analysis is crucial in breeding for quality traits. The objectives of this study were to (i) evaluate grain yield performance of introduced zinc-enhanced, provitamin A, normal and quality protein maize lines across stress and non-stress environments in Zimbabwe, (ii) assess the presence of GEI and (iii) identify high yielding and stable lines that could be used for developing Zn-enhanced hybrids with improved seed producibility. Additive main effects and multiplicative interaction (AMMI) and genotype plus genotype × environment interaction (GGE) biplot analyses were used for stability analysis. GEI effects were highly significant (P ≤ 0.01) for grain yield. Grain yields for the inbred lines ranged from 1.28 to 3.5 t ha−1. The Zn donor G11 (ITZN313) had the highest grain yield of 3.5 t ha−1 across environments, whereas the normal check G24 (CZL1111) had the lowest grain yield. G2 (CLWQHZN14), G4 (CLWQHZN19), G8 (OBATANPA6), G11 (ITZN313) and G18 (CML546) were stable and high yielding and can be used for developing Zn-enhanced hybrids. Five mega-environments were identified, clearly separating stress and non-stress environments. E11 (Chisumbanje WW) was the most discriminating and representative test environment and could be used to identify superior genotypes.